The examination of mediating role of distributed leadership in the relationship between school structure and accountability - Orhan, Mustafa; Ozdemir, Tuncay Yavuz (Izzet Kara, 2024)
The aim of this study was to investigate the relationship between school structure, distributed leadership and accountability of school administrators. Relational survey design was adopted in the study. 444 elementary school teachers working in Aziziye, Paland & ouml;ken and Yakutiye in Erzurum participated in the study. In sample selection, stratified sampling method was used. In data collection, the Enabling School Structure Scale, the Distributed Leadership Scale and the Accountability Behavior Scale for School Administrators were used. The data were analyzed using SPSS 23.0 for preliminary statistical analyses, LISREL 8.80 for Structural Equation Modeling (SEM), and the PROCESS macro for SPSS v3.3 for mediation analyses. In data analysis, Pearson Product -Moment Correlation Analysis, Bootstrap Analysis, and SEM were used. Furthermore, a mediation analysis was conducted to investigate whether distributed leadership played a mediating role in the relationship between school structure and accountability. The results revealed that coercive bureaucracy had a negative effect on accountability and distributed leadership while enabling bureaucracy had a positive effect on accountability and distributed leadership. Furthermore, the analysis revealed a positive effect of distributed leadership on accountability. This study revealed the mediating role of distributed leadership in the effect of coercive and enabling bureaucracy on accountability. In other words, it was found that the coercive and enabling bureaucracy had direct and indirect effects on accountability. Finally, a number of recommendations were made to educators, policy makers and researchers based on these findings.
Keywords: School structure; Coercive bureaucracy; Accountability; Enabling bureaucracy; Distributed leadership